Islamic Social Finance And Poverty Alleviation Efforts (Contextual Al-Qur'an Tafsir Study) - Putra, Trisno Wardy; Abubakar, Achmad; Irham, Muhammad (LP2M IAIN Palopo, 2024)
Poverty is a crucial problem in human life. The Qur'an also explains some of the causes of poverty. This research aims to examine the role of Islamic social finance as an effort to alleviate poverty from the perspective of Qur'anic interpretation. This research uses a qualitative approach with a literature study approach, which examines sources related to the theme raised. This method also uses the science of interpretation by examining the verses of the Qur'an contextually. The results showed that in the Qur'an, poverty can occur due to several causes, whether it comes from oneself, the environment, and the state. In the implementation of the role of Islamic social finance as an effort to alleviate poverty, it has made a major contribution even though it has not been significant. This is due to management that has not been maximized. However, it has been proven in history that Islamic social finance is able to alleviate poverty.